2014
DOI: 10.5430/jnep.v5n1p1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perinatal meditation on pregnant Chinese women in Hong Kong: A randomized controlled trial

Abstract: Objective: To assess the effects of Perinatal Meditation on pregnant Chinese women in Hong Kong. Design: A prospective longitudinal randomized control quantitative study. Data were collected using the Prenatal Distress Questionnaire, Prenatal Coping Inventory, Edinburgh Postnatal Depression Scale, Body-Mind-Spirit Well-Being Inventory (BM-SWBI) and salivary cortisol. Data were collected during first visit, 36th weeks pregnant, 5 th weeks and 5 th months after delivery. Settings: Perinatal meditation program (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 220 publications
2
9
0
1
Order By: Relevance
“…Labour worry was comparable to study norms. Pregnancy experience uplift scores were higher and hassles scores lower than previously found but intensity of experiences was comparable to previous samples (Chan 2014).…”
Section: Mothers-to-besupporting
confidence: 83%
“…Labour worry was comparable to study norms. Pregnancy experience uplift scores were higher and hassles scores lower than previously found but intensity of experiences was comparable to previous samples (Chan 2014).…”
Section: Mothers-to-besupporting
confidence: 83%
“…Matvienko-Sikar and Dockray (2017) emphasized that positive psychological intervention reduced the PSS of 46 Australian pregnant women. Chan (2015) improved pregnancy stress and pregnancy outcomes with six sessions of mindfulness mediation intervention in 123 Chinese pregnant women. Richter et al (2012) reported the early effect of cognitive behavioral group intervention on daily stress and cortisol in pregnant women with symptoms of stress, anxiety, and depression (Richter et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the review focused exclusively on antenatal rather than postnatal populations and also did not include analysis of several recent randomised-controlled trials of MBIs (e.g. [ 32 , 33 , 34 , 35 , 36 , 37 ]). Therefore, it remains uncertain as to whether or not the evidence to date suggests that MBIs are effective for perinatal populations and this question would benefit from a meta-analysis which could comprehensively draw together and summarise this evidence.…”
Section: Introductionmentioning
confidence: 99%